Integrating Experiential Learning and Character Education: The Effectiveness of a Hiking Game Technique Module - Ambarwati, Ambarwati; Wangid, Muhammad Nur (Jurnal Bimbingan dan Konseling Terapan, 2024)
This study investigates the effectiveness of a hiking game technique group guidance module aimed at enhancing self-resilience among adolescents, a critical response to the challenge of juvenile delinquency exacerbated by insufficient educational and environmental support systems. Through a structured development process influenced by the Borg & Gall model, this research integrates experiential learning with character education, providing adolescents with the tools to navigate physical, cognitive, and emotional challenges. The module, which underwent rigorous validation by experts in guidance and counseling, is structured around activities that foster teamwork, problem-solving, and emotional management, thus proving effective in promoting resilience and character development in young individuals. The study's findings demonstrate the module's appropriateness and efficacy, suggesting that outdoor educational activities can be a vital part of contemporary educational strategies to address the multifaceted needs of adolescents, especially in promoting mental health and behavioral adjustment. This approach aligns with the goals of strengthening character education through practical, real-world applications, although the COVID-19 pandemic posed limitations to direct field testing.